Prognostic impact of serial measurements of serum-free light chain assay throughout the course of newly diagnosed multiple myeloma treated with bortezomib-based regimens. Issue 9 (1st September 2016) - Tacchetti, Paola; Cavo, Michele; Rocchi, Serena; Pezzi, Annalisa; Pantani, Lucia; Brioli, Annamaria; Testoni, Nicoletta; Terragna, Carolina; Zannetti, Beatrice Anna; Mancuso, Katia; Marzocchi, Giulia; Borsi, Enrica; et al.
Abstract: We retrospectively investigated the role of serial serum-free light chain (sFLC) evaluations in 150 multiple myeloma (MM) patients treated with first-line bortezomib-based regimens. Baseline sFLC ratio (sFLCR) identified three groups of patients – normal, lightly abnormal (<100), and highly abnormal (≥100) – with different progression-free survival (PFS: 3-year estimate 72% versus 61% versus 44%, respectively, p  = 0.03). Moreover, the achievement of a normal sFLCR correlated with extended PFS (49 versus 17 months, p  < 0.0001) and overall survival (75 versus 43 months, p  < 0.0001) as compared with abnormal sFLCR, a gain maintained in a multivariate analysis for PFS. At relapse, a high sFLCR was associated with earlier start of salvage therapy compared with sFLCR <100 (3-month probability: 89% versus 64%, p  = 0.0426). In 20% of patients, sFLC escape preceded the conventional relapse by a median of 3.8 months. Our results highlight the role of sFLC assay in the prognosis and follow-up of MM.